Is oxidative stress evaluated in viable human spermatozoa a marker of good semen quality? - Traini, Giulia; Tamburrino, Lara; Vignozzi, Linda; Baldi, Elisabetta; Marchiani, Sara (Frontiers in Endocrinology, 2022)
Background: Oxidative stress is defined as the unbalance between reactive oxygen species (ROS) production and antioxidant defences. Whereas low levels of ROS are necessary for physiological sperm functions, high levels impair fertility damaging membranes, proteins and DNA. In this study, we used two probes, CellROX® Orange and Dihydroethidium (DHE), which reveal different intracellular ROS species, to evaluate the association between the percentage of oxidized viable spermatozoa and sperm functions. Methods: The percentage of oxidized spermatozoa was evaluated by flow cytometry with the two probes concomitantly with standard semen parameters and sperm DNA fragmentation (sDF, by TUNEL/PI). Phosphatidylserine membrane exposure, caspase 3,7 activity, sperm kinematic parameters and hyperactivated motility were evaluated by Annexin V, FLICATM and CASA system respectively. Results: Oxidized viable spermatozoa, evaluated with both probes, were positively associated with sperm basal parameters and negatively with sDF. Also, we found that a consistent percentage of CellROX® positive viable spermatozoa were selected from whole semen during swim up procedure. Double staining of CellROX® Orange with Annexin V and FLICATM demonstrated that viable oxidized spermatozoa do not show apoptotic features. Conclusion: Overall, our results suggest that CellROX® Orange and DHE allows identification of the viable oxidized sperm fraction related to better performances.